Deskripsi Sarana dan Prasarana Laboratorium Fisiska SMA Negeri di Kota Kendari - Siti Aminah; Vivi Hastuti; Mardiana Napirah (Jurnal Penelitian Pendidikan Fisika, 2022)
Facilitation in education is something that can support teaching learning process at school. Laboratory is one the important facilitation because the lab is a place where student can practice their skill through demonstration, experiment and development of knowledge. This study aims to describe the availability of facilities and infrastructure for the State High School Physics laboratory in Kendari City. Method used in this study is a qualitative descriptive method. This research does not provide manipulation treatment or modifier of independent variables, but describes a condition as it is. Based on the types of descriptive research, this research includes the type of research with the observation method. In accordance with the problems studied, namely to see the facilities and infrastructure of the State High School Physics laboratory in Kendari City, the researchers used the observation method which aims to obtain information about the description of the State High School Physics laboratory facilities and infrastructure in Kendari City. The population in this study were all public high schools in Kendari City which consisted of 10 districts and 11 schools. Sampling in this study was conducted using purposive sampling technique. Purposive sampling is used because the determination of the sample with consideration only takes schools that have physics laboratories. So that the samples in this study are SMA Negeri 2 Kendari, SMA Negeri 4 Kendari, SMA Negeri 5 Kendari, SMA Negeri 10 Kendari and SMA Negeri 11 Kendari. The results of this study indicate that the facilities and infrastructure of the State High School Physics laboratory in Kendari City are categorized as pretty good and in quite appropriate with Permendiknas No. 24 of 2007.